Human Talent Management in Academia: In the Face of the Challenge of Information and Communication Technologies - Vargas Prado, Kelly; Jurado Enriquez, Elizabeth Lizbel; Talla Linderman, Magdalena Cecilia; Huamán Narvay, José; Campos Sobrino, Medalith del Rocio; Campos Martinez, Silvana Rosario (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The purpose of this study is to determine the influence of human talent management as a value element on the academic productivity of university professors in Peru. This is a basic, cross-sectional, explanatory study; the sample consisted of 110 university professors, selected by non-probabilistic convenience sampling, who responded to two questionnaires evaluating human talent management and academic productivity. The results showed that human talent management as a value element significantly influences academic productivity by 57.0%.